Fiscal News and Macroeconomic Volatility - Benjamin Born; Alexandra Peter; Johannes Pfeifer (University of Bonn, Bonn Graduate School of Economics (BGSE), 2011)
This paper analyzes the contribution of anticipated capital and labor tax shocks to business cycle volatility in an estimated New Keynesian DSGE model. While fiscal policy accounts for 12 to 20 percent of output variance at business cycle frequencies, the anticipated component hardly matters for explaining fluctuations of real variables. Anticipated capital tax shocks do explain a sizable part of inflation and interest rate fluctuations, accounting for between 5 and 15 percent of total variance. In line with earlier studies, news shocks in total account for 20 percent of output variance. Further decomposing this news effect, we find that it is mostly driven by stationary TFP and non-stationary investment-specific technology.
Keywords: E32; E62; C11; 330; Anticipated Tax Shocks; Sources of Aggregate Fluctuations; Bayesian Estimation